Diversity and Agronomic Performance of Lupinus mutabilis Germplasm in European and Andean Environments - Gulisano, Agata; Alves, Sofia; Rodriguez, Diego; Murillo, Angel; van Dinter, Bert-Jan; Torres, Andres F.; Gordillo-Romero, Milton; Torres, Maria de Lourdes; Neves-Martins, João; Paulo, Maria-João; Trindade, Luisa M. (Frontiers in Plant Science, 2022)
The introduction of Lupinus mutabilis (Andean lupin) in Europe will provide a new source of protein and oil for plant-based diets and biomass for bio-based products, while contributing to the improvement of marginal soils. This study evaluates for the first time the phenotypic variability of a large panel of L. mutabilis accessions both in their native environment and over two cropping conditions in Europe (winter crop in Mediterranean region/ summer crop in North-Central Europe), paving the way for the selection of accessions adapted to specific environments. The panel of 225 accessions included both germplasm pools from the Andean region and breeding lines from Europe. Notably, we report higher grain yield in Mediterranean winter-cropping conditions (18 g/plant) than in the native region (9 g/plant). Instead, North European summer-cropping conditions appear more suitable for biomass production (up to 2kg/plant). The phenotypic evaluation of 16 agronomical traits revealed significant variation in the panel. Principal component analyses pointed out flowering time, yield and architecture related traits as the main factors explaining variation between accessions. The Peruvian material stands out among the top yielding accessions in Europe, characterized by early lines with high grain yield (e.g. LIB065, LIB072, LIB155). Bolivian and Ecuadorian material appears more valuable for the selection of genotypes for Andean conditions and for biomass production in Europe. We also observe that flowering time in the different environments is influenced by temperature accumulation. Within the panel, it is possible to identify both early and late genotypes, characterized by different thermal thresholds ( 600-700 °C and 1000-1200 °C GDD, respectively). Indications on top-yielding and early/late accessions, heritability of morpho-physiological traits and their associations with grain yield are reported and remain largely environmental specific, underlining the importance of selecting useful genetic resources for specific environments. Altogether, these results suggest that the studied panel holds the genetic potential for the adaptation of L. mutabilis to Europe and set the basis for initiating a breeding program based on exploiting the variation described herein.